Topology optimization of double and triple layer grid structures using a modified gravitational harmony search algorithm with efficient member grouping strategy. (August 2016) - Mashayekhi, Mostafa; Salajegheh, Eysa; Dehghani, Milad
Highlights: A hybrid optimization approach is developed for topology optimization of structures. An efficient member grouping strategy is proposed for optimization of skeletal structures. The proposed MGHSA method was very competitive with other meta-heuristic methods. Abstract: An efficient modified gravitational harmony search algorithm (MGHSA) for topology optimization of double and triple layer grid structures is presented in the article. In MGHSA, the best agents in each iteration are identified and each of them is considered as a group leader. Other agents are randomly located in these groups. To determine the new agents' positions, only the group leader applies force to the other agents in the group. Also, a novel member grouping strategy is included in the optimization algorithm. Optimization results demonstrate the efficiency of the novel MGHSA algorithm and member grouping strategy developed in this study.